2019
DOI: 10.1002/ange.201901456
|View full text |Cite
|
Sign up to set email alerts
|

A Nucleophilicity Scale for the Reactivity of Diazaphospholenium Hydrides: Structural Insights and Synthetic Applications

Abstract: Nucleophilicity parameters (N, sN) of a group of representative diazaphospholenium hydrides were derived by kinetic investigations of their hydride transfer to a series of reference electrophiles with known electrophilicity (E) values, using the Mayr equation log k2=sN(N+E). The N scale covers over ten N units, ranging from the most reactive hydride donor (N=25.5) to the least of the scale (N=13.5). This discloses the highest N value ever quantified in terms of Mayr's nucleophilicity scales reported for neutra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Building on our previous work 59 , we envisioned that diazaphospholenes of super hydricity 60 62 may provide a good chance to realize HDF of trifluoromethylalkenes via an S N 2’ path 63 . A preliminary attempt indicated that the reaction of α-trifluoromethyl-styrene 2a with diazaphospholene 1 primarily gave the hydrophosphination intermediate A .…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Building on our previous work 59 , we envisioned that diazaphospholenes of super hydricity 60 62 may provide a good chance to realize HDF of trifluoromethylalkenes via an S N 2’ path 63 . A preliminary attempt indicated that the reaction of α-trifluoromethyl-styrene 2a with diazaphospholene 1 primarily gave the hydrophosphination intermediate A .…”
Section: Resultsmentioning
confidence: 98%
“…Catalyst 1 has been synthesized and characterized in our previous work 59 , 73 , 74 . Trifluoromethyl alkenes 2 were synthesized according to references (see Supplementary Information for details).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, the potent nucleophilicity of the DAP-hydrides was quantified according to the Mayr nucleophilicity scale by Cheng and co-workers. 16 Their systematic study on the kinetics of hydride addition to several benchmark electrophiles established that 1 is, at the time of writing, the most nucleophilic hydride donor ever quantified, with a nucleophilicity parameter (N) of 25.54 (cf. for NaBH 4 , N = 14.74).…”
Section: Synthesis and Structural Propertiesmentioning
confidence: 99%
“…[2] For, instance, diazaphospholene hydrides (DAP-Hs) are powerful nucleophiles and weakly basic organic hydride donors. [3] They efficiently reduce carbonyls [4] and, in conjugate fashion, α,β-unsaturated amides, [5] esters, [5b, 6] ketones, [5] and acids (Scheme 1). [7] A σ-bond metathesis between the alkoxysubstituted DAPs and pinacol borane (HBpin) regenerating DAP-H rendered these processes catalytic.…”
mentioning
confidence: 99%